Trust in Electronic Marketing - Gaurav, Kunal (Indian Journal of Marketing, 2010)
Electronic marketing is a relatively new concept and crept into the business vocabulary in around 1970s. It refers to the flawless application of information technology from the point of origin to the ultimate destination of the products along with the entire value chain; the business processes are carried out electronically and intended to accomplish the business goals effectively and efficiently. With the advent and mass acceptance of Radio, Television, Mobile, World Wide Web; electronic media have become the dominant marketing force and an important part of our life. E-commerce further led to the emergence of the "market space" - a virtual world of information paralleling the real marketplace of goods and services - that enables marketers to manage content, context, and infrastructure in new and different ways, thereby providing novel sources of competitive advantage (Rayport and Sviokla, 1994). With electronic marketing, one can think of business across the globe that was not possible earlier. In recent years, increasing numbers of businesses have been using the internet in their marketing efforts. The internet is unique because it offers dual advantage to businesses; it can be thought of as a market as well as a medium. Electronic Marketing can be interactive and relatively inexpensive than Traditional Marketing. Now-a-days, manufacturers of physical goods as well service providers (e.g. travel agents, real estate agents, business consultants, chartered accountants etc.) have found the internet to be key to their success. Whatever the potential of the channel for completing transactions, it is obvious that various marketing functions are present with which the internet can assist and play a very important role in establishing competitive advantage (Robbins, 2000). In the same line of thought, Rettie (2002) strongly advocated that the internet is creating a "virtual culture" which has its own form of manners (netiquette), members of society (netizens) and method of expressing emotions (emoticons) for those who have matured in the net generation.